Sistem Informasi Persediaan Barang Jadi pada PT. SAP Berbasis Desktop - Octanza, Tahta Rizaldi; Sudrajat, Ari; Ginting, Gerinata (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2024)
The aim of this research is to carry out a series of stages starting from analyzing, designing, implementing and testing the Finished Goods Inventory Information System at PT. SAP. The research method used is the waterfall method and the analysis used is PIECES analysis, with system testing using black-box testing. The programming language used is Microsoft Visual Visual Studio with Microsoft Access as the database. It is known that the resulting inventory information system is a system solution that has been running previously, the recording process of which is still semi-computerized using Microsoft Excel so that the inventory data processing process is not appropriate. Based on the results of the information system that has been created, it can be concluded that, with a computerized and integrated database system, it can help and make it easier for warehouse admins to input goods data, incoming goods data and outgoing goods data that occur at PT. SAP, minimizes errors and makes data input easier. Based on the overall calculation of the (UAT) User Acceptance Test by the user, the system testing using Black-box received an assessment of 91.43% which was categorized as Very Good.